Improving fiscal policy in the EU : the case for independent forecasts - Jonung, Lars.; Larch, Martin; European Commission : Directorate-General for Economic and Financial Affairs (Brussels ; Belgium : European Commission: Directorate-General for Economic and Financial Affairs, 2004)
The evidence from several euro-area countries demonstrates the existence of a forecast bias in the budgetary process, which negatively affects fiscal performance. To remedy this bias, we suggest that forecasting should be assigned to an authority independent from the ministry of finance and the government, with the task of producing unbiased projections of growth and other variables crucial for the budgetary process.
Internal paper
Economic Papers